2003
DOI: 10.1590/s1517-83822003000500016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the electrolytic treatment on Bacillus subtilis

Abstract: Conventional processes of water disinfection can generate toxic composites. It is the case of the trihalomethanes (carcinogenic) formed in the contact of chlorine with organic substances present in the water. The electrolytic treatment can be a substitute for the chlorination process without the need for addition of chemical substances to the process. The effect of the electrolytic treatment using carbon cathode on the viability of the microorganism Bacillus subtilis was tested to determine the death process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The intended products are responsible for the disinfection of water [30]. These studies are consistent with the study by Rahmani in 2005 [28]. Rahmani showed that increasing the voltage from 8 to 25 V and reducing the distance from 8 to 2 cm leads to an increase in the efficiency of E. coli bacteria removal at the rate of 1 colony/liter [10].…”
Section: E Coli < Bacillus Subtilis < Bacillus Subtilis Sporessupporting
confidence: 81%
See 1 more Smart Citation
“…The intended products are responsible for the disinfection of water [30]. These studies are consistent with the study by Rahmani in 2005 [28]. Rahmani showed that increasing the voltage from 8 to 25 V and reducing the distance from 8 to 2 cm leads to an increase in the efficiency of E. coli bacteria removal at the rate of 1 colony/liter [10].…”
Section: E Coli < Bacillus Subtilis < Bacillus Subtilis Sporessupporting
confidence: 81%
“…Also, increasing the contact time up to 15-75 min increased the process efficiency [27]. Rahmani et al investigated bacterial elimination by electrolysis and found that the amount of removal would depend on the voltage and duration of electrolysis and that the removal efficiency is higher at higher voltages [28]. The bacterial mortality during the electrochemical process involves the production of chemical disinfectants such as chlorine and ozone, flux transfer in the bacteria-electrode interface, the destruction of the cytoplasmic membrane and increased cell membrane permeability [29].…”
Section: E Coli < Bacillus Subtilis < Bacillus Subtilis Sporesmentioning
confidence: 99%
“…Tolentino-Bisneto e Bidóia 22 trabalharam com a eletrólise de Bacillus subtilis e observaram que as células ficavam com material de lise e tamanho comum reduzido, além de também ter sido observado um extravasamento do citoplasma. Após 30 min de eletrólise, a parede das células apresentou buracos e parte do citoplasma escoou como resultado da eletroporação irreversível.…”
Section: Resultsunclassified
“…Tolentino-Bisneto and Bidoia (2003) sugested that the discharge from the electrodes causes microorganism's death by cellular lysis due to the electroporation in the cell membrane.…”
Section: Electrochemical Disinfection In Phosphatebuffered Solutionmentioning
confidence: 99%